Chemistry of nanocrystalline oxide materials combustion synthesis, properties and applications - Patil, K. C. (World Scientific, 2008)
Nano-oxide materials lend themselves to applications in a wide variety of emerging technological fields such as microelectronics, catalysts, ceramics, coatings, and energy storage. However, developing new routes for making nano-based materials is a challenging area for solid-state materials chemists. This book does just that by describing a novel method for preparing them. The authors have developed a novel low-temperature, self-propagating synthetic route to nano-oxides by the solution combustion and combustible precursor processes. This method provides the desired composition, structure, and properties for many types of technologically useful nanocrystalline oxide materials like alumina, ceria, iron oxides, titania, yttria, and zirconia, among others.
Keywords: Metallic oxides.; Nanocrystals.; Nanostructured materials.; elektronické knihy; electronic books